Răspunsuri

2014-04-24T00:45:19+03:00
2x-y+3z=4  /-3
3x+4y-z=-5  /2

-6x+3y-9z=-12
6x+8y-2z=-10
/11y-11z=-22
11(y-z)=-22
y-z=-2
y=-2+z

x+5y-5z=-9                           2x-y+3z=4
x+5(-2+z)-5z=-9                   2x-(-2+z)+3z=4
x-10-5z-5z=-9                        2x+2-z+3z=4
x-10z=1                                 2x+2z=2
x=1+10z                                 2(x+z)=2
x=1+10z                                    x+z=1
                                                 1+10z+z=1
                                                         11z=0                    z=0
y=-2+0
y=-2
x=1+10*0
x=1